2020
DOI: 10.3389/fonc.2020.00920
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Modulate Drug Resistance-Related Mechanisms in Hepatocellular Carcinoma

Abstract: Primary liver cancer [hepatocellular carcinoma (HCC)] is one of the most common malignant tumors worldwide, causing serious health threats because of its high morbidity and mortality, rapid growth, and strong invasiveness. Patients with HCC frequently develop resistance to the current chemotherapeutic drugs, and this is largely attributed to the high-level heterogeneity of the tumor tissue. MicroRNAs (miRNAs) are a group of master regulators for multiple physiological and pathological processes and play import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 125 publications
0
23
0
Order By: Relevance
“…HCC is the most prevalent primary liver cancer, accounting for 70-85% of all cases with primary liver cancer, while metastasis is the main death cause of HCC [13]. miRNAs are critically involved in gene expression regulation at both transcriptional and posttranscriptional levels during the initiation and progression of various types of cancer, including HCC [14]. Increasing studies have shown that miRNAs can influence HCC occurrence by regulating oncogenes and tumor suppressor genes [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…HCC is the most prevalent primary liver cancer, accounting for 70-85% of all cases with primary liver cancer, while metastasis is the main death cause of HCC [13]. miRNAs are critically involved in gene expression regulation at both transcriptional and posttranscriptional levels during the initiation and progression of various types of cancer, including HCC [14]. Increasing studies have shown that miRNAs can influence HCC occurrence by regulating oncogenes and tumor suppressor genes [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) can directly suppress the target gene translation by binding to the 3′ untranslated region (3′ UTR) of the target mRNA (Bazavar et al., 2020; Liang et al., 2020; Singh et al., 2012). Dysregulation of miRNAs promotes malignant phenotypes, such as tumour growth, metastasis and appearance of MDR through regulating downstream targets and associated pathways (Mutlu et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated by our group and others that microRNAs (miRs) represent powerful small RNA molecules that modulate drug resistance related features in HCC [ 10 , 24 ]. In recent years, miR-622 has emerged as one of the most promising tumorsuppressive microRNAs, which is underscored by multiple studies addressing its potent role in diverse types of cancer [ 6 , 10 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%